Deciphering structure-composition-efficacy transformation in processed Fuzi: an integrated SEM, XRD, metabolomics, and pharmacodynamics approach - Yang, Yang; Wei, Xuemei; Zhang, Shuya; Li, Yun; Wu, Jiazhen; Cai, Suhua; Wang, Biren; Yang, Zhiming; Yang, E.; Cao, Junling; Chen, Qinhua; Chen, Guihong (Frontiers in Chemistry, 2025)
BackgroundAconiti Lateralis Radix Praeparata (Fuzi), a vital yet toxic herbal medicine, faces significant challenges in standardization due to varied processing methods that undermine detoxification efficacy and hinder therapeutic optimization.MethodsAn integrative analytical approach combining scanning electron microscopy (SEM), X-ray diffraction (XRD), metabolomics, and pharmacodynamic evaluation was employed to investigate the structural, compositional, and functional transformations during Fuzi processing.ResultsSEM imaging and XRD data revealed that the morphological breakdown of starch granules varied according to processing technique. Metabolomics analysis based on mass spectrum identified 57 diterpenoid alkaloids, including 12 bioactive components, whose levels fluctuated across nine processing variants. Pharmacodynamic profiling revealed distinct efficacy-safety trade-offs across these variants, underscoring the pivotal role of processing methods in determining clinical risk profiles and therapeutic indices.ConclusionThis study elucidated the structure-composition-efficacy correlations in Fuzi processing, highlighting the relationship between starch reorganization, alkaloid modification, and therapeutic outcomes. These insights offer a mechanistic basis for refining traditional processing protocols, optimizing detoxification and therapeutic retention, and advancing standardization in herbal medicine.